2007
DOI: 10.1061/(asce)1076-0342(2007)13:4(261)
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Energy Use and Greenhouse Gas Emissions Inventory for Water Treatment Systems

Abstract: Given the rising concerns over scarce energy resources and global climate change, life-cycle inventories focusing on energy use and greenhouse gas ͑GHG͒ emissions were developed for the City of Toronto municipal water treatment system ͑WTS͒. Three processes within the facility use phase of the life cycle were considered: Chemical production, transportation of materials, and water treatment plant operation. The impacts of chemical manufacturing were estimated using the economic input-output life-cycle assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(95 citation statements)
references
References 27 publications
4
88
0
3
Order By: Relevance
“…This finding is similar to Racoviceanu et al (2007) as the water treatment facilities phase has contributed the most GHG emission which is 0.12 kg CO 2 -eq per m 3 whereas the total GHG emission from the total energy use for a water treatment system is 0.13 g CO 2 -eq per m …”
Section: Carbon Footprint Of Different Stages Of Water Productionsupporting
confidence: 80%
See 3 more Smart Citations
“…This finding is similar to Racoviceanu et al (2007) as the water treatment facilities phase has contributed the most GHG emission which is 0.12 kg CO 2 -eq per m 3 whereas the total GHG emission from the total energy use for a water treatment system is 0.13 g CO 2 -eq per m …”
Section: Carbon Footprint Of Different Stages Of Water Productionsupporting
confidence: 80%
“…A similar study carried out by Mrayed and Leslie (2009) found that the greenhouse gas emissions from the generation of electricity for the operation of seawater desalination plant accounted for a large proportion (95 %) of the total greenhouse gas emissions, followed by chemicals production (4 %). Also a North American study found that 90 % of the GHG emissions came from electricity generation and the rest from chemicals (Racoviceanu et al 2007). …”
Section: Identification Of Hot Spotmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the articles [1,2] in big cities between 7 and 10% of total energy spent in the whole UWC is lost in the sewer systems and the primary energy consumption for collection and transportation of wastewater and other water equals 105 MJ/cap/year in the Netherlands, 530 MJ/cap/year in USA, 380 MJ/cap/year in Toronto and 74 MJ/cap/year in Sydney. A lot of this energy is in form of heat from water heating in households and from industrial processes [2][3][4].…”
Section: Introductionmentioning
confidence: 99%